SIRT3 deficiency promotes lung fibrosis by augmenting alveolar epithelial cell mitochondrial DNA damage and apoptosis. Issue 6 (3rd March 2017) - Jablonski, Renea P.; Kim, Seok‐Jo; Cheresh, Paul; Williams, David B.; Morales‐Nebreda, Luisa; Cheng, Yuan; Yeldandi, Anjana; Bhorade, Sangeeta; Pardo, Annie; Selman, Moises; Ridge, Karen; Gius, David; et al.
ABSTRACT: Alveolar epithelial cell (AEC) mitochondrial dysfunction and apoptosis are important in idiopathic pulmonary fibrosis and asbestosis. Sirtuin 3 (SIRT3) detoxifies mitochondrial reactive oxygen species, in part, by deacetylating manganese superoxide dismutase (MnSOD) and mitochondrial 8‐oxoguanine DNA glycosylase. We reasoned that SIRT3 deficiency occurs in fibrotic lungs and thereby augments AEC mtDNA damage and apoptosis. Human lungs were assessed by using immunohistochemistry for SIRT3 activity via acetylated MnSOD K68 . Murine AEC SIRT3 and cleaved caspase‐9 (CC‐9) expression were assayed by immunoblotting with or without SIRT3 enforced expression or silencing. mtDNA damage was measured by using quantitative PCR and apoptosis via ELISA. Pulmonary fibrosis after asbestos or bleomycin exposure was evaluated in 129SJ/wild‐type and SIRT3‐knockout mice (Sirt3 − / − ) by using fibrosis scoring and lung collagen levels. Idiopathic pulmonary fibrosis lung alveolar type II cells have increased MnSOD K68 acetylation compared with controls. Asbestos and H2 O2 diminished AEC SIRT3 protein expression and increased mitochondrial protein acetylation, including MnSOD K68 . SIRT3 enforced expression reduced oxidant‐induced AEC OGG1 K338/341 acetylation, mtDNA damage, and apoptosis, whereas SIRT3 silencing promoted these effects. Asbestos‐ or bleomycin‐induced lung fibrosis, AEC mtDNA damage, and apoptosis in wild‐type mice were amplified in Sirt3 − / − animals. These data suggest a novel role for SIRT3 deficiency in mediating AEC mtDNA damage, apoptosis, and lung fibrosis.—Jablonski, R. P., Kim, S.‐J., Cheresh, P., Williams, D. B., Morales‐Nebreda, L., Cheng, Y., Yeldandi, A., Bhorade, S., Pardo, A., Selman, M., Ridge, K., Gius, D., Budinger, G. R. S., Kamp, D. W. SIRT3 deficiency promotes lung fibrosis by augmenting alveolar epithelial cell mitochondrial DNA damage and apoptosis. FASEB J. 31, 2520–2532 (2017). www.fasebj.org